Pain interference mediates the association between epigenetic aging and grip strength in middle to older aged males and females with chronic pain - Peterson, Jessica A.; Crow, Joshua A.; Johnson, Alisa J.; Meng, Lingsong; Rani, Asha; Huo, Zhiguang; Foster, Thomas C.; Fillingim, Roger B.; Cruz-Almeida, Yenisel (Frontiers in Aging Neuroscience, 2023)
Objective: To explore the associations among self-reported pain, grip strength, and epigenetic aging in those with chronic pain. Methods: Participants (57.91 ± 8.04 years) with chronic pain completed pain questionnaires, a blood draw and handgrip task. An epigenetic clock associated with knee pain (DNAmGrimAge) was used, and the subsequent difference of epigenetic age from chronological age (DNAmGrimAge-Difference) was calculated. Results: Exploratory pathway analyses (moderated-mediation) revealed that pain intensity mediated the association between DNAmGrimAge-difference and grip strength in males only (β =-0.1115; CI [-0.2929, -0.0008]) and pain interference mediated the association between DNAmGrimAge-difference and grip strength in males (β =-0.1401; CI [-0.3400, -0.0222]), and females (β =-0.024; CI [-0.2918, -0.0020]). Conclusions: Chronic pain may accelerate epigenetic aging processes that then may ultimately influence grip strength in older age males and females. Chronic pain could be a symptom of the aging body thus contributing to declines in musculoskeletal function in later life.